The role of endocrine-disrupting chemicals in male fertility decline - Henriques, Magda Carvalho (2021)
Endocrine-disrupting chemicals (EDCs) are exogenous compounds with natural or anthropogenic origin omnipresent in the environment. These compounds disrupt endocrine function through interaction with hormone receptor or alteration of hormone synthesis. Humans are environmentally exposed to EDCs through the air, water, food and occupation. During the last decades, there has been a concern that exposure to EDCs may contribute to an impairment of human reproductive function. EDCs affect male fertility at multiple levels, from sperm production and quality to the morphology and histology of the male reproductive system. It has been proposed that exposure to EDCs may contribute to an impairment of sperm motility, concentration, volume and morphology and an increase in the sperm DNA damage. Moreover, EDCs exert reproductive toxicity inducing structural damage on the testis vasculature and blood-testis barrier and cytotoxicity on Sertoli and Leydig cells. This chapter will explore the effects of EDCs in male reproductive system and in the decline of male fertility.